The neural bases of framing effects in social dilemmas - Julian Macoveanu; Thomas Zoëga Ramsøy; Martin Skov; Hartwig R. Siebner; Toke R. Fosgaard (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2015)
Human behavior in social dilemmas is strongly framed by the social context, but the mechanisms underlying this framing effect remains poorly understood. To identify the behavioral and neural responses mediating framing of social interactions, subjects underwent functional Magnetic Resonance Imaging while playing a Prisoners Dilemma game. In separate neuroimaging sessions, the game was either framed as a cooperation game or a competition game. Social decisions where subjects were affected by the frame engaged the hippocampal formation, precuneus, dorsomedial prefrontal cortex and lateral temporal gyrus. Among these regions, the engagement of the left hippocampus was further modulated by individual differences in empathy. Social decisions not adhering to the frame were associated with stronger engagement of the angular gyrus and trend increases in lateral orbitofrontal cortex, posterior intraparietal cortex, and temporopolar cortex. Our findings provide the first insight into the mechanisms underlying framing of behavior in social dilemmas, indicating increased engagement of the hippocampus and neocortical areas involved in memory, social reasoning and mentalizing when subjects make decisions that conform to the imposed social frame.
Keywords: C90; 330; Social reasoning; prisoners dilemma; fMRI; framing